Faktor yang Berperan terhadap Anemia pada Pekerja Perempuan Usia Produktif di Indonesia, Riset Kesehatan Dasar 2013 - Tana, Lusianawaty; Banjuradja, Ivan (Badan Penelitian dan Pengembangan Kesehatan, 2018)
Anemia is still a problem for public health, especially in women. In 2010, the prevalence of anemia in the world was 32.9%. This article presents further analysis to determine the factors that contribute to anemia in female workers of productive age in Indonesia. Data source was Basic Health Research (Riskesdas) year 2013, with sampleâs criteria: women, working, age of 15-64 years old, and not pregnant. The dependent variable was anemia based on Hemoglobin examination by Hemocue.The independent variables included individual characteristics, shelter, disease history, pregnancy and miscarriage, and nutritional status. Data were analyzed using complex sampling, 0.05 significance level, and 95% confidence interval. The number of samples that met the criteria was 8612 people. Factors contributed to anemia were age, number of pregnancy, and nutritional status (OR adjusted 1.53-1.83). Anemia increased 1.8 and 1.6 times at age of 55-64 years old and 45-54 years compared to age 15-24years. Anemia increased 1.47 times in those with children more than 5 compared with female had no children. Anemia increased 1.27 times in low nutritional status compared to normal. Factors contributing to the occurrence of anemia in female workers were age, number of children and nutritional status (OR adjusted 1.53-1.83). Improved nutritional status and increased knowledge of nutritious foods should be attempted to reduce the incidence of anemia.Â AbstrakAnemia masih merupakan masalah bagi kesehatan masyarakat terutama pada perempuan. Prevalensi anemia di dunia tahun 2010 dilaporkan 32,9%. Analisis lanjut ini bertujuan menentukan faktor yang berperan terhadap anemia pada pekerja perempuan usia produktif di Indonesia. Sumber data adalah Riset Kesehatan Dasar (Riskesdas) tahun 2013, kriteria sampel: perempuan, status bekerja, umur 15-64 tahun, dan tidak hamil. Variabel terikat adalah anemia berdasarkan pemeriksaan hemoglobin dengan hemocue. Variabel bebas meliputi karakteristik individu, tempat tinggal, riwayat penyakit, kehamilan dan keguguran, dan indeks massa tubuh. Data dianalisis dengan kompleks sampel, tingkat kemaknaan 0,05 dan confidence interval 95%. Jumlah sampel yang memenuhi kriteria sebanyak 8.612 orang. Anemia meningkat 1,8 dan 1,6 kali pada umur 55-64 tahun dan 45-54 tahun dibandingkan umur 15-24 tahun. Anemia meningkat 1,47 kali pada yang memiliki anak > 5 orang dibandingkan perempuan yang tidak punya anak. Anemia meningkat 1,27 kali pada status gizi kurang dibandingkan status gizi normal. Faktor berperan dalam terjadinya anemia pada pekerja perempuan adalah umur, jumlah anak, dan status gizi (OR adjusted 1,53-1,83). Perbaikan status gizi dan peningkatan pengetahuan tentang makanan bergizi perlu diupayakan untuk menurunkan kejadian anemia.